Peran Sistem Manajemen Kinerja di PT. Garindo Sejahtera Abadi Cabang Pamekasan - Ferdy Adriansyah Hadhinata; Ahmad Dhani Syahrudin; Muhammad Akirom Wildan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The performance management system in this company functions as a strategic tool to achieve organizational goals by managing performance assessments in an accountable and transparent manner. Implementing this system allows companies to develop employee potential, increase employee motivation and commitment, and achieve overall business goals. A performance management system not only focuses on annual appraisals, but also includes planning, measuring and developing employee performance. By integrating company goals with employee performance, PT. Garindo Sejahtera Abadi is able to create a productive and innovative work environment. This states that a performance management system helps in identifying employee potential, providing constructive feedback, and designing training programs that suit development needs. This research uses research methods, namely theoretical studies, previous literature, interviews and field observations to collect relevant data regarding the role of performance management systems at PT. Garindo Sejahtera Abadi Pamekasan Branch.